Sustainable suppliers evaluation in the waste management sector: the case of a leading Sicilian enterprise. Issue 11 (2022) - Cinnirella, Valentina; Carpitella, Silvia; Coco, Antonio; Frangiamore, Davide Domenico Maria; de Geronimo, Rossella Pezzino
Abstract: Sustainable waste management is a fundamental service within the concept of smart cities development as well as social welfare and economic growth. With this recognition, the careful preliminary screening and consequent selection of reliable green suppliers is crucial. This process should be formalised and performed with relation to the various commodity sub-sectors that are relevant for companies operating within the field of reference. To such an aim, the present paper approaches the problem of supplier selection by proposing a Multi-Criteria Decision-Making (MCDM) model based on the integrated use of the Analytic Hierarchy Process (AHP) and the Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS). Such a methodological combination has been widely and successfully proposed in literature for the supplier selection problem. However, to the best of the authors' knowledge, this is the first time that the mentioned MCDM tool is applied to suppliers of a real company operating in the waste management sector and according to pre-defined commodity sub-sectors of interest. This study aims to also highlight the different importance of technical, economic and environmental aspects towards a sustainable optimisation of such a fundamental city service as waste management is.